2012
DOI: 10.1186/1476-511x-11-114
|View full text |Cite
|
Sign up to set email alerts
|

A potential synbiotic product improves the lipid profile of diabetic rats

Abstract: BackgroundPrevious studies showed that intake of yacon or some lactic acid bacteria was able to inhibit the development of diabetes mellitus, by reducing glucose and associated symptoms, for example, the lipid profile.ObjectiveThe purpose of this study was to assess the consumption influence of a potential symbiotic product of soybean and yacon extract and fermented Enterococcus faecium CRL 183 and Lactobacillus helveticus ssp jugurti 416 in reducing blood glucose and lipid levels in an animal model.MethodsDia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
4
14
1
2
Order By: Relevance
“…One other study was excluded as it reported the same outcomes published previously in line with other new but irrelevant results [38]. Six other studies were excluded as they evaluated the effects of synbiotics [39][40][41][42][43] or prebiotics [44]. Three animal reports that were published in languages other than English were excluded as well [45][46][47].…”
Section: Probiotics and Diabetesmentioning
confidence: 99%
“…One other study was excluded as it reported the same outcomes published previously in line with other new but irrelevant results [38]. Six other studies were excluded as they evaluated the effects of synbiotics [39][40][41][42][43] or prebiotics [44]. Three animal reports that were published in languages other than English were excluded as well [45][46][47].…”
Section: Probiotics and Diabetesmentioning
confidence: 99%
“…Recently, probiotic consumption is shown to decrease serum liver enzymes [9,10]. Previous studies have shown that some probiotic bacteria had the ability to improve serum lipid profiles [11][12][13][14][15]. However, there is limited elucidation on its mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…AYE was administered to prebiotic (G4) and synbiotic (G5) groups. Yacon root (purchased in a local marketing) was pasteurized at 95°C/15 min immediately after yacon cutting, and yacon was ground to obtain an aqueous extract (Pauly-Silveira et al, 2010;Roselino et al, 2012). FOS content in AYE was determined with fructan assay kit (Megazyme, Ireland) (Korakli, Hinrichs, Ehrmann, & Vogel, 2003).…”
Section: Probiotic and Prebiotic Preparationmentioning
confidence: 99%